The Analysis of Factors in Children’s Dietary Patterns That Affect Physical Fitness - Thatit Nurmawati; Anita Rahmawati; Yeni Kartika Sari; Oni Puji Lestari (STIKes Patria Husada Blitar, 2024)
Fitness for children is related to optimal physical condition. Fitness influences mental and social development, especially children's concentration and learning abilities. Fitness must be maintained to support activities. Diet is a supporting factor for children's physical fitness. Diet is the foundation for long-term health. The research aimed to determine factors related to eating patterns that influence children's physical fitness. The research design was cross-sectional. The research population was school children aged 10-12 years totaling 96 students in 2023 using the total sampling method. The independent variables were BMI (Body Massa Index), physical activity, and rest, and the dependent variable was the child's physical fitness. The instrument used the Physical Activity Questionnaire to measure activity, eating patterns using Food Frequency, rest using The Pittsburgh Sleep Quality Index, and physical fitness, calculated using the Technical Guidelines for Health Screening and Periodic Examination of School-Age Children and Adolescents in 2018. The analysis test used linear regression (P<0.05) to determine the relationship between factors related to eating patterns and influencing children's physical fitness. The results of the study showed that there was no relationship between BMI (p 0.661), physical activity (0.783), and rest (p 0.756) on eating patterns. An eating pattern is a significant mediator for physical activity and rest but not for BMI (p 0.733) on children's physical fitness. Rest (p 0.000) and physical activity (p 0.004) influence children's physical fitness. BMI does not measure the position and location of fat, so people with the same BMI have different fitness levels.